Feasibility Analysis of Pakcoy (Brassica chinensis L.) Cultivation with Hydroponic System Using Several Types of Planting Media - Sischa Febriani Yamesa Away; Ririn Fatma Nanda; Kusmiati (Open Global Scientific Journal, 2022)
Pakcoy is a leaf vegetable of high economic value and rich in nutritional content so it is greatly demanded by the public. This study aims to analyze the effect of using several types of planting media on the growth and yield of pakcoy plants with a hydroponic system; analyze the type of planting media that mostly affect the growth and yield of pakcoy plants; and analyze the feasibility of pakcoy cultivation with a hydroponic system using several types of planting media. This research was conducted from February to March 2021 in Kandang Lamo, Sarilamak, Harau Subdistrict, Lima Puluh Kota Regency, West Sumatra. Data were analyzed using a complete randomized design (CRD). There were three treatments using several types of planting media with three replications simultaneously covering a total of 81 plant samples. Data were analyzed with ANOVA, then continued with DMRT 15%. Financial economic analysis was measured by calculating revenue value, R/C ratio, BEP, and profitability ratio. The results reveal that the treatment of several types of planting media has not significantly affected the number of leaves and leaf’s width, plant’s height and plant’s fresh weight. The highest average value is resulted by the brick fragments planting medium treatment. It is proven from the average results on the leaf’s width (11.04 cm) and the number of leaves (17.03) at the age of 4 weeks after planting. The highest production yield value (131.24 gr) is resulted by the rockwool planting medium treatment. The results of the financial economic analysis show that the pakcoy cultivation business with a hydroponic system using various types of planting media is feasible to be continued. It is proven from the variable analysis of the business profit and loss statement on the parameter of R/C ratio and the profitability ratio.